The Role of Creativity and Innovation in The Success of Small Businesses in East Nusa Tenggara - Minsel R. Munni; Eugenia S. Mine; Axel A. Patty; Petra L.M. Bria; Enike Tje Yustin Dima (Yayasan Pendidikan Islam Al-Matani, 2026)
This study aims to analyze the role of creativity and innovation in the success of small businesses in East Nusa Tenggara. The method used in this research is a literature review with a qualitative descriptive approach, utilizing various scientific journals as data sources. The results show that creativity plays a role in generating new ideas that can be developed into business opportunities, while innovation plays a role in implementing these ideas into products or services that have economic value. Furthermore, creativity and innovation simultaneously exert a significant influence on business success. Therefore, business actors must continuously cultivate creativity and innovation to survive and compete in the modern era.